EXISTENCE OF Stelechocarpus burahol (Bl.) Hook.F. & Th. IN WILDERNESS ZONE, BANDE ALIT RESORT, MERU BETIRI NATIONAL PARK - Umiyah (The East Java Biological Society, 2005)
Many researchers (Botanists, Systematists, Taxonomists, etc.), especially who concern in plant conservation are afraid about the existence of Stelechocarpus burahol (Bl.) Hook.f. & Th., family Annonaceae. Because, the plant is becoming rare and facing extinction. Information about the species is so limited and difficult to get. Fortunately, based on the preliminary study of the population shows that it can be found in Wilderness Zone, Bande Alit Resort, Meru Betiri National Park. The mapping of the species disperse in this location was also done.